Controlling of grid connected photovoltaic lighting system with fuzzy logic - ERDAL, HASAN; EKREN, NAZMİ; SAĞLAM, ŞAFAK (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
In this study, DC electrical energy produced by photovoltaic panels is converted to AC electrical energy and an indoor area is illuminated using this energy. System is controlled by fuzzy logic algorithm controller designed with 16 rules. Energy is supplied from accumulator which is charged by photovoltaic panels if its energy would be sufficient otherwise it is supplied from grid. During the 1-week usage period at the semester time, 1.968 kWh energy is used from grid but designed system used 0.542 kWh energy from photovoltaic panels at the experiments. Energy saving is determined by calculations and measurements for one education year period (9 months) 70.848 kWh. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Illumination; Photovoltaic energy; Fuzzy logic; Energy saving